Pengaruh Harga terhadap Keputusan Pembelian Helm - Achmad Ali Yafi K; Didit Darmawan (Universitas Kristen Indonesia Toraja, 2025)
Motorcycles have become an important part of the daily lives of most Indonesians. By utilizing bicycles as a means of transportation, time and distance constraints can easily be overcome, especially in cities full of traffic jams. On the other hand, motorcycles are vehicles that are at high risk of traffic accidents and provide the least protection for their riders, especially their heads, which are the most valuable human assets. As a result, a good and safe helmet must meet safety and comfort standards. Consumer decisions to buy a helmet can be influenced by price. Price is considered a fundamental factor that can influence a buyer's decision to choose. The results of the study revealed that the price variable significantly influences purchasing decisions. The main objective of this literature study is to analyze and synthesize previous research findings related to the influence of price on helmet purchasing decisions and identify factors that influence helmets on helmet product purchasing decisions. This study uses a qualitative method with a literature study approach.